THE USE OF CAKE APPLICATION TO IMPROVE STUDENTS’ READING COMPREHENSION AT SMA NEGERI 9 NORTH HALMAHERA - Novanda Sari Hi. Abang; Anwar Ismail; Asrul M. Syawal (Jurnal Bilingual, 2022)
The purpose of this research is to find out the ability of students in reading at SMA Negeri 9 Halut. This study used a qualitative method with 20 students. Data collection was carried out by pre-test and post-test in the form of multiple choices. The results showed that students obtained very poor results (very poor in the pre-test. It can be seen from the average score of 47 out of 20 students and in the post-test students obtained sufficient with an average score of 70 out of 20 students. For grades the maximum pre-test students get very bad scores with a score of 47 and in the post-test students get sufficient with a score of 70 out of 20 students. .5 in the pre-test and 8.1 in the post-test of 20 students.Finally, the variation in the pre-test of students was 67 and the post-test was 112.2 of 20 students.